1997
DOI: 10.1590/s0034-89101997000400007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de flebotomíneos (Diptera: Psychodidae) em foco de leishmaniose visceral no Estado de Mato Grosso do Sul, Brasil

Abstract: INTRODUÇÃO: Nas Américas, Lutzomyia longipalpis tem sido incriminada como vetora da leishmaniose visceral em, praticamente, todas as áreas de ocorrência dessa parasitose. A notificação de casos humanos a partir de 1980 e a presença de cães com aspecto sugestivo de leishmaniose visceral no Município de Corumbá, Estado de Mato Grosso do Sul, Brasil, levaram a investigações entomológicas na área, com o objetivo de identificar a população de flebotomíneo vetora. MATERIAL E MÉTODO: A pesquisa foi realizada no peri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
88
5
37

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 20 publications
(5 reference statements)
9
88
5
37
Order By: Relevance
“…In the states of Ceará, Bahia, and Mato Grosso do Sul, a higher population density of phlebotomine sand flies has been observed during the rainy periods (Deane 1956, Sherlok & Guilton 1969, Galati et al 1997, while in Costa Rica, higher densities occur in the dry periods (Zeledón et al 1984) In Amazônia Maranhense, there have been abundant phlebotomine species during the rainy periods, others in dry periods and several species irregularly distributed throughout the year, L. longipalpis and L. whitmani (Rebêlo et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…In the states of Ceará, Bahia, and Mato Grosso do Sul, a higher population density of phlebotomine sand flies has been observed during the rainy periods (Deane 1956, Sherlok & Guilton 1969, Galati et al 1997, while in Costa Rica, higher densities occur in the dry periods (Zeledón et al 1984) In Amazônia Maranhense, there have been abundant phlebotomine species during the rainy periods, others in dry periods and several species irregularly distributed throughout the year, L. longipalpis and L. whitmani (Rebêlo et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…L. cruzi has been implicated in VL transmission in MS (Santos et al 1998), being found naturally infected in the municipality of Jaciara, in MT (unpublished observations). Other phlebotomine species, such as L. forattini and L. almerioi, may also be associated with the disease in MS, both anthropophilic, although has not been evidenced its vectorial ability (Galati et al 1997, whereas in the state of Para, L. antunesi is considered an alternative VL vector (Lainson & Rangel 2003). In Colombia, L. evansi has been reported to be the most likely VL vector (Travi et al 1990).…”
mentioning
confidence: 99%
“…Mais recentemente, Lutzomyia cruzi foi também incriminado como vetor no Estado de Mato Grosso do Sul 15 . A espécie L. longipalpis está bem adaptada ao ambiente peridomiciliar, alimentando-se em uma grande variedade de hospedeiros vertebrados, entre aves, homem e outros animais silvestres ou domésticos.…”
unclassified